National screening for anxiety and depression in Saudi Arabia 2022 - Alhabeeb, Abdulhameed Abdullah; Al-Duraihem, Rashed Abdullah; Alasmary, Saeed; Alkhamaali, Zaied; Althumiri, Nora A.; BinDhim, Nasser F. (Frontiers in Public Health, 2023)
Background Mental health disorders, such as major depressive disorder (MDD) and generalized anxiety disorder (GAD), represent a significant public health concern in Saudi Arabia. This study aims to provide a recent mental health screening prevalence, including anxiety and depression screening in the general public and to explore the associated risk factors. Methods A cross-sectional study was conducted, employing a phone interview survey with 6,015 participants, using a quota sampling strategy to ensure equal representation of both sexes and administrative regions. The study assessed the prevalence of MDD and GAD risk and examined demographic, socioeconomic, and lifestyle factors associated with these mental health disorders. Results The national prevalence of people at risk of MDD and GAD were found to be 12.7 and 12.4%, respectively. Low diagnosis and treatment rates were observed, with only 1.5 and 0.5% of participants currently diagnosed and treated for depression and anxiety, respectively. Risk factors for MDD and GAD included female sex, lower education and income levels, smoking, and waterpipe use. Protective factors included physical activity, participation in volunteering activities and the practice of daily hobbies in the last 30 days. Conclusion The relatively high prevalence of MDD and GAD risk and low diagnosis and treatment rates in Saudi Arabia emphasize the need for increased mental health promotion, early detection, and treatment accessibility. The study highlights the importance of addressing modifiable risk factors and fostering protective factors through targeted interventions. Future research should focus on longitudinal associations, potential mediators and moderators, and the development of culturally appropriate and evidence-based interventions to enhance mental health outcomes in the region.